2002
DOI: 10.1097/00130535-200205000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Cerumen, Hearing, and Cognition in the Elderly

Abstract: This study found a majority of residents admitted to the SNF had cerumen impaction. Evaluation of hearing and mental status following removal of cerumen resulted in a statistically significant improvement in hearing and cognition when compared with controls. Removal of cerumen is a relatively safe and easy procedure that can be done at minimal cost and provide a significant benefit to residents of a SNF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…This frequency was quite low compared with Western countries. [2][3][4]10 The prevalence of wet type cerumen in the present study was 25.5%, and the incidence of wet cerumen with impaction and wet cerumen without impaction was not significantly different. The cause of a non-significant incidence of wet cerumen impaction in the present study might be due to the low participants.…”
Section: Discussionmentioning
confidence: 45%
See 3 more Smart Citations
“…This frequency was quite low compared with Western countries. [2][3][4]10 The prevalence of wet type cerumen in the present study was 25.5%, and the incidence of wet cerumen with impaction and wet cerumen without impaction was not significantly different. The cause of a non-significant incidence of wet cerumen impaction in the present study might be due to the low participants.…”
Section: Discussionmentioning
confidence: 45%
“…8,9 Moore et al reported significant improvement of hearing and MMSE score after cerumen removal. 10 Similarly, Oron et al reported a significant difference in participants' Raven's Standard Progressive Matrices Test scores before and after cerumen removal.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…13 Moreover, excessive or impacted cerumen in high-risk populations, such as the elderly and developmentally delayed, is underdiagnosed and likely undertreated. 10,14,15 The target patient for this guideline is over 6 months of age with a clinical diagnosis of cerumen impaction.…”
Section: Introductionmentioning
confidence: 99%